2011
DOI: 10.1371/journal.ppat.1002153
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Thermometer Controls Temperature-Dependent Transcription of Flagellar Motility Genes in Listeria monocytogenes

Abstract: Facultative bacterial pathogens must adapt to multiple stimuli to persist in the environment or establish infection within a host. Temperature is often utilized as a signal to control expression of virulence genes necessary for infection or genes required for persistence in the environment. However, very little is known about the molecular mechanisms that allow bacteria to adapt and respond to temperature fluctuations. Listeria monocytogenes (Lm) is a food-borne, facultative intracellular pathogen that uses fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 54 publications
3
83
0
Order By: Relevance
“…These results are compatible with Lmo1722 affecting the expression of motility genes at the transcriptional level. The regulation of Listeria motility is complex (26,33,34). Both the gene encoding the repressor of motility (mogR) and the gene encoding the positive regulator of motility (gmaR) were downregulated in the ⌬lmo1722 strain compared to the wild-type strain (data not shown), indicating that Lmo1722 functions upstream of these regulators.…”
Section: Resultsmentioning
confidence: 98%
“…These results are compatible with Lmo1722 affecting the expression of motility genes at the transcriptional level. The regulation of Listeria motility is complex (26,33,34). Both the gene encoding the repressor of motility (mogR) and the gene encoding the positive regulator of motility (gmaR) were downregulated in the ⌬lmo1722 strain compared to the wild-type strain (data not shown), indicating that Lmo1722 functions upstream of these regulators.…”
Section: Resultsmentioning
confidence: 98%
“…33,34,47 Strains of L. monocytogenes lacking both DegU and MogR still repress motility in a temperature-dependent fashion and this finding, combined with ΔlysPGS retention of motility at 37 °C, indicates that formation of LysPG and LysCL may contribute to motility repression. The findings presented in this study suggest that LysPG and LysCL do not affect flagellin localization but that they could either be necessary for adequate regulation of the membrane potential used to drive the flagellar motor or for assembly of a motor protein required for motility.…”
Section: Lyspg and Lyscl In L Monocytogenes Are Involved In Regulatimentioning
confidence: 90%
“…32 GmaR becomes unstable at the non-permissive growth temperature (37 °C) and dissociates from the motility operon repressor, MogR, thus resulting in downregulation of motility. [33][34][35] Investigation using immunoblotting against the flagellin-encoding flaA gene indicated that there were no detectable differences in localization of flagellin between the wild-type and the ΔlysPGS strain at either 37 °C or 30 °C. However, flagellin was detected to exhibit altered gel mobility in the ΔlysPGS strain compared with the wild-type strain indicating a potential difference in the O-acetylation, polymerization, or activity state of the protein (data not shown).…”
Section: Loss Of Lyspgs Causes No Significant Effect On Protein Localmentioning
confidence: 99%
“…The MogR-GmaR heterocomplex is destabilized and disrupted upon a thermal upshift to 37°C due to a conformational change in GmaR. Hence, the actual thermosensor in this process is not the DNA-binding protein MogR, but the interacting protein GmaR [155]. The response regulator DegU has also shown to be involved in the thermo-induced regulation of the flagellar motility genes [156,157].…”
Section: Thermo-induced Conformational Changes Abolish Dna-bindingmentioning
confidence: 99%
“…Transcriptional activator of virulence genes; binds to DNA as homodimer at 20-25°C, defolds partially at higher temperatures and looses its DNA binding capacity; multisensor: salicylate prevents DNA-binding of RovA [137,139,142] Listeria monocytogenes MogR:GmaR MogR binds to flagella genes and represses transcription at 37°C; anti-repressor GmaR binds MogR at 30°C; in complex no repression; GmaR misfolds at 37°C and MogR:GmaR complex disassembles [150,152,153,155] Agrobacterium tumefaciens VirA Two-component system VirAG activates transcription of vir genes only below 32°C; sensor kinase VirA changes conformation at high temperatures and is inactive [4] Pseudomonas syringae CorS Two-component system CorSR activates transcripttion of phytotoxin biogenesis genes at 18°C; at 28°C: rearrangements of the transmembrane domains of the sensor kinase CorS prevent autophosphorylation and/or phosphotransfer to response regulator [177,178] Streptococci M-like proteins Class C proteins bind to plasma proteins low temperatures as coiled coils; homodimers disrupt at 37°C; C-repeats seem to be thermosensitive Cedervall 1995Cedervall 1997 …”
Section: Salmonella Enterica Tlpamentioning
confidence: 99%